Validation of Physics Kit Based on Sensor and PjBL Model to Improve Students' Digital Literacy, Science Process Skills, and Learning Outcomes - Fahmi Firdaus; Susilawati; Ahmad Harjono (Jurnal Penelitian Pendidikan IPA, 2024)
The development of of physics kit based on sensor and PjBL model has been carried out to improve the digital literacy, science process skills, and learning outcomes of students. This development aims to describe the validation of physics kit teaching materials that are suitable for use in learning activities. The development model design used is 4D which consists of definition, design, development and dissemination stages. This research is limited to the development stage. Validation activities have been completed in the development process. The validity of of physics kit based on sensor and PjBL model was assessed by 3 competent experts who are competent at Mataram University. In addition to the validity of the physics kit, there are several learning tools that are assessed for validity to support the quality of the kit developed. Some of these learning tools include lesson plans, worlsheets, test instruments for digital literacy, science process skills, and learning outcomes. The validation results showed that the physics kit received an average score of 93.35%, the lesson plans 87.50%, the student worksheets 94.17%, the digital literacy instrument 87.54%, the science process skills instrument 92.59%, and the learning outcome instrument 88.63%. Based on these results, all components were categorized as "Very Valid". These findings indicate that the physics kit based on sensors and the PjBL model is highly valid and can be effectively used in science learning activities at school.